Impact of BRCA Mutation Status on Tumor Dissemination Pattern, Surgical Outcome and Patient Survival in Primary and Recurrent High-Grade Serous Ovarian Cancer: A Multicenter Retrospective Study by the Ovarian Cancer Therapy-Innovative Models Prolong Survival (OCTIPS) Consortium - Glajzer, Jacek; Castillo-Tong, Dan Cacsire; Richter, Rolf; Vergote, Ignace; Kulbe, Hagen; Vanderstichele, Adriaan; Ruscito, Ilary; Trillsch, Fabian; Mustea, Alexander; Kreuzinger, Caroline; Gourley, Charlie; Gabra, Hani; et al. (Annals of Surgical Oncology, 2022)
Background: This study seeks to evaluate the impact of breast cancer (BRCA) gene status on tumor dissemination pattern, surgical outcome and survival in a multicenter cohort of paired primary ovarian cancer (pOC) and recurrent ovarian cancer (rOC).
CRIS-Team WoS Importer:2022-09-16